2021
DOI: 10.1007/s00431-021-03968-6
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis in COVID-19 times: a nearly absent disease?

Abstract: Stay-at-home orders, physical distancing, face masks and other non-pharmaceutical interventions (NPIs) do not only impact COVID-19, but also the dynamics of various other infectious diseases. Bronchiolitis is a clinically diagnosed viral infection of the lower respiratory tract, and causes a yearly seasonal wave of admissions in paediatric wards worldwide. We counted 92,5% less bronchiolitis hospitalisations in Antwerp before the expected end of the peak this year (of which only 1 RSV positive), as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
151
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(191 citation statements)
references
References 12 publications
17
151
0
4
Order By: Relevance
“…A time series analysis by Angoulvant et al in France reported a significant decrease in airborne-disseminated infectious diseases, including bronchiolitis (−63.5%), during the COVID19 outbreak [ 6 ]. Data from Belgium strengthen this evidence, outlining an early ending of the 2019–2020 bronchiolitis season, together with a nearly absent burden of disease in the first months of the epidemic season of 2020–2021 [ 15 ]. Our data point in the same direction, given that no bronchiolitis cases were reported in our center during the entire 2020–2021 season.…”
Section: Discussionmentioning
confidence: 94%
“…A time series analysis by Angoulvant et al in France reported a significant decrease in airborne-disseminated infectious diseases, including bronchiolitis (−63.5%), during the COVID19 outbreak [ 6 ]. Data from Belgium strengthen this evidence, outlining an early ending of the 2019–2020 bronchiolitis season, together with a nearly absent burden of disease in the first months of the epidemic season of 2020–2021 [ 15 ]. Our data point in the same direction, given that no bronchiolitis cases were reported in our center during the entire 2020–2021 season.…”
Section: Discussionmentioning
confidence: 94%
“…An unprecedented low incidence of respiratory viral infections was reported during the coronavirus disease 2019 (COVID- 19) pandemic [1][2][3][4][5][6]. The likely contributing factors included universal mask use, school closures, travel restrictions, bans on mass gatherings and other public health and physical distancing measures to control COVID-19.…”
mentioning
confidence: 99%
“…Recently, van Brusselen et al 1 reported that in the 2020-2021 European winter bronchiolitis and particularly its main responsible RSV had practically disappeared by the time its usual annual peak was expected, just when the second wave of the pandemic began. But, as the season is not completely over, they acknowledge the concern for a late spring/summer peak.…”
mentioning
confidence: 99%